2012
DOI: 10.1007/jhep12(2012)014
|View full text |Cite
|
Sign up to set email alerts
|

Non-extremal black hole microstates: fuzzballs of fire or fuzzballs of fuzz?

Abstract: Abstract:We construct the first family of microstate geometries of near-extremal black holes, by placing metastable supertube probes inside certain scaling supersymmetric smooth microstate geometries. These fuzzballs differ from the classical black hole solution macroscopically at the horizon scale, and for certain probes the fluctuations between various fuzzballs will be visible as thermal noise far away from the horizon. We discuss whether these fuzzballs appear to infalling observers as fuzzballs of fuzz or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 72 publications
2
118
0
Order By: Relevance
“…11 What is the form of the density matrix in the fine-grained Hilbert space? In fact, as is well known, we can find a basis for the fine-grained Hilbert space so that the density matrix looks exactly like (5.5) with zeroes in the other places.…”
Section: Jhep10(2013)212mentioning
confidence: 99%
See 1 more Smart Citation
“…11 What is the form of the density matrix in the fine-grained Hilbert space? In fact, as is well known, we can find a basis for the fine-grained Hilbert space so that the density matrix looks exactly like (5.5) with zeroes in the other places.…”
Section: Jhep10(2013)212mentioning
confidence: 99%
“…Even though the principle of equivalence suggests that there is nothing special about the horizon of a large black hole, there have been several speculations that quantum gravity effects cause the interior to be modified into a fuzzball [1][2][3][4][5], and more recently, that the horizon of an "old black hole" is replaced by a firewall [6]. (See also [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].) These latter proposals originate, not from direct calculations in quantum gravity, but rather in arguments that the information paradox (in various incarnations) cannot be solved without modifying the geometry at, or behind the horizon.…”
Section: Introductionmentioning
confidence: 99%
“…Last but not least, anti-branes have been used to construct solutions dual to microstates of the D1-D5-p near-extremal black hole [53,54], and in the probe approximation these anti-branes appear to be metastable, much like in all other anti-branes studied in this way [3,33,55]. However, on general D1-D5 CFT grounds we expect these microstate solutions to be unstable, and this instability gives the Hawking radiation rate of the dual CFT microstate [56].…”
Section: Jhep02(2015)146mentioning
confidence: 99%
“…Besides the above exact solutions, there exists a proposal to build large classes of microstate geometries for near-extremal black holes by placing negatively-charged probe supertubes in supersymmetric solutions [42,43]. The action of these supertubes has metastable minima, but it has recently been shown that these solutions are classically unstable to decay into supersymmetric microstates [44].…”
Section: Jhep02(2016)073mentioning
confidence: 99%